"توظيف الامثال الشعبية في روايات "محمد مفلاح - درار, أمال (كلية الأدب العربي والفنون, 2024)
يعد الكاتب الجزائري ''محمد مفلاح'' من أبرز رواد الرواية العربية المعاصرة الذين وظفوا الأمثال الشعبية بشكل لافت في أعمالهم الروائية وقد حضيت هذه الظاهرة باهتمام نقدي كبير من قبل الدارسين، والباحثين مما جعلها موضوعا متكررا في الدراسات الأكاديمية والمقالات النقدية ومعرفة لغوية أو تزيين أسلوبي بل تجاوز ذلك ليكون أداة فاعلة لخدمة الأهداف السردية والجمالية والفكرية لرواياته حيث تضفي الأمثال الشعبية على اللغة سمة الواقعية والصدق مما يقربه من لغة التخاطب اليومية ويكسب رواياته سمة الأصالة والانتماء إلى البيئة الثقافية الجزائرية، أما على النص الروائي فلها لمسة من الجمال والفنية مما يثري تجربة القارئ ويمتعه، وتمثل جسرا للتواصل مع التراث الثقافي الجزائري مما يؤثر النص الروائي ويضفي عليه عمقا تاريخيا وثقافيا The Algerian writer "Mohamed Meflah" is one of the most prominent pioneers of the contemporary Arab novel who employed popular proverbs in a striking way in their novels. This phenomenon has received great critical attention from scholars and researchers, which made it a recurring topic in academic studies, critical articles, linguistic knowledge, or stylistic embellishment. Rather, it has gone beyond that to be an effective tool to serve the narrative, aesthetic, and intellectual goals of his novels, as popular proverbs give the language a realism and honesty, which brings it closer to the language of daily communication and gives his novels a characteristic of authenticity and belonging to the Algerian cultural environment. As for the novel text, it has a touch of beauty and artistry, which enriches the reader's experience and entertains him, and represents a bridge for communication with the Algerian cultural heritage, which affects the novel text and gives it historical and cultural depth.
Keywords: مثل شعبي،رواية، تراث ثقافي، سرد: proverb, novel, cultural heritage, narrative